PENGARUH FINANCIAL DISTRESS DAN PROFITABILITAS TERHADAP ACCOUNTING PRUDENCE PADA PERUSAHAAN SUBSEKTOR KONSTRUKSI BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - ROSEDIANA, RANNY; FRIYANTO; HARITSAR, YOSAR (Akademika : Jurnal Manajemen, Akuntansi, dan Bisnis., 2024)
The purpose of this research is to find out the effects of financial distress and profitability on accounting prudence. The population in this research is the whole of the construction and building subsector companies listed on the Indonesian Stock Exchange (IDX) in the period 2019–2022. The data source used is the secondary data of the company’s financial report obtained from the official website of the Indonesian Stock Exchange. The type of research used is quantitative research. The sampling method of this research uses purposive sampling, and based on the criteria that have been determined, 15 companies were selected from 25 over 4 years of research, thus obtaining 60 data observations. The research used multiple regression analysis using the SPSS version 25 application with a significance level of 0.05. Based on the results of the research, financial distress has a positive but not significant effect on accounting prudence. While profitability has a significant negative effect on accounting prudence. Furthermore, financial distress and profitability simultaneously have a significant effect on accounting prudence.